Genotype-dependent responses of pepper endophytes to soil microbial community shifts induced by allyl isothiocyanate fumigation - Wenfeng Tian; Wenfeng Tian; Qiuxia Wang; Aocheng Cao; Dongdong Yan; Yuan Li; Zhoubin Liu; Bozhi Yang; Wensheng Fang (Frontiers in Microbiology)
IntroductionAllyl isothiocyanate (AITC) has demonstrated efficacy as a soil fumigant, effectively controlling soil-borne pathogens and nematodes. Although AITC has a significant effect on soil microbial communities, whether fumigation affects the production of crop endophytes is unclear.MethodsIn this study, AITC was used to fumigate the soil, and the response of endophytic bacteria (in roots, stems, and leaves) in different pepper genotypes (Xiangla359, La Xuan, Shuang Jiao) was investigated.ResultsFumigation with AITC significantly increased soil microbial diversity, stimulated the growth of Actinomycetota, and inhibited Pseudomonadota. However, the effects on endophytic bacteria varied among pepper varieties. Specifically, fumigation significantly reduced microbial diversity in the roots and leaves of Xiangla359, but had no significant effect on La Xuan and Shuang Jiao. Furthermore, the growth-promoting effect of AITC was most pronounced in Xiangla359.ConclusionOur results suggest that while AITC fumigation significantly alters soil microbial diversity and composition, its effects on crop endophytes are genotype-dependent. These findings provide insight into the complex interactions between soil microbial communities and crop endophytes in response to soil fumigation.